Asymmetric α-amination of β-keto esters using a guanidine–bisurea bifunctional organocatalyst - Odagi, Minami; Yamamoto, Yoshiharu; Nagasawa, Kazuo (Beilstein Journal of Organic Chemistry, 2016)
An asymmetric α-amination of β-keto esters with azodicarboxylate in the presence of a guanidine–bisurea bifunctional organocatalyst was investigated. The α-amination products were obtained in up to 99% yield with up to 94% ee.
Keywords: α-amination; bifunctional catalyst; guanidine; hydrogen-bonding catalyst; urea

(untitled) - Maruoka, K.; Ooi, T. (Chem. Rev., 2003)

(untitled) - Nájera, C.; Sansano, J. C. (Chem. Rev., 2007)

(untitled) - Bergmeier, S. C. (Tetrahedron, 2000)

(untitled) - Yet, L. (Angew. Chem., Int. Ed., 2001)

(untitled) - Greck, C.; Drouillat, B.; Thomassigny, C. (Eur. J. Org. Chem., 2004)

(untitled) - Janey, J. M. (Angew. Chem., Int. Ed., 2005)

(untitled) - Vilaivan, T.; Bhanthumnavin, W. (Molecules, 2010)

(untitled) - Smith, A. M. R.; Hii, K. K. (Chem. Rev., 2011)

(untitled) - Marigo, M.; Juhl, K.; Jørgensen, K. A. (Angew. Chem., Int. Ed., 2003)

(untitled) - Terada, M.; Nakano, M.; Ube, H. (J. Am. Chem. Soc., 2006)

(untitled) - Huber, D. P.; Stanek, K.; Togni, A. (Tetrahedron: Asymmetry, 2006)

(untitled) - Kang, Y. K.; Kim, D. Y. (Tetrahedron Lett., 2006)

(untitled) - He, R.; Wang, X.; Hashimoto, T.; Maruoka, K. (Angew. Chem., Int. Ed., 2008)

(untitled) - Jung, S. H.; Kim, D. Y. (Tetrahedron Lett., 2008)

(untitled) - Lan, Q.; Wang, X.; He, R.; Ding, C.; Maruoka, K. (Tetrahedron Lett., 2009)

(untitled) - Konishi, H.; Lam, T. Y.; Malerich, J. P.; Rawal, V. H. (Org. Lett., 2010)

(untitled) - Chosh, S.; Nandakumar, M. V.; Krautscheid, H.; Schneider, C. (Tetrahedron Lett., 2010)

(untitled) - Azuma, T.; Kobayashi, Y.; Sakata, K.; Sasamori, T.; Tokitoh, N.; Takemoto, Y. (J. Org. Chem., 2014)

(untitled) - Sohtome, Y.; Nagasawa, K. (Synlett, 2010)

(untitled) - Sohtome, Y.; Nagasawa, K. (Chem. Commun., 2012)

(untitled) - Odagi, M.; Furukori, K.; Watanabe, T.; Nagasawa, K. (Chem. – Eur. J., 2013)

(untitled) - Odagi, M.; Furukori, K.; Yamamoto, Y.; Sato, M.; Iida, K.; Yamanaka, M.; Nagasawa, K. (J. Am. Chem. Soc., 2015)

(untitled) - Satyanarayana, T.; Abraham, S.; Kagan, H. B. (Angew. Chem., Int. Ed., 2009)

(untitled) - Sohtome, Y.; Takemura, N.; Takada, K.; Takagi, R.; Iguchi, T.; Nagasawa, K. (Chem. – Asian J., 2007)

(untitled) - Sohtome, Y.; Shin, B.; Horitsugi, N.; Takagi, R.; Noguchi, K.; Nagasawa, K. (Angew. Chem., Int. Ed., 2010)

(untitled) - Sohtome, Y.; Tanaka, S.; Takada, K.; Yamaguchi, T.; Nagasawa, K. (Angew. Chem., Int. Ed., 2010)

(untitled) - Sohtome, Y.; Shin, B.; Horitsugi, N.; Noguchi, K.; Nagasawa, K. (Chem. – Asian J., 2011)